VERBAL INTERACTION PATTERNS IN A PHYSICS CLASS USING EXPERIMENTAL ACTIVITIES - Almeida Raboni, Paulo Cesar de [UNESP]; Lima, Guilherme da Silva (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2018)
In this paper we present the main results of an investigation of verbal interactions motivated by use of experimental activities in physics classes in high school. Through the selection of a case study, we follow the lessons of a physics teacher for four months. In our results, we found a complex enunciative network that develops through breaks and incorporated ideas, built on a common reference. We seek to understand these interactions using the contributions proposed by Bakhtin circle. These results allow us to state that the experimental activities potentially have much to contribute to the triggering of verbal interactions in class, encouraging the expression of many voices, expand significantly the quantity and quality of the interpretations and hypotheses raised by students.
Keywords: Physics teaching; Verbal interactions; Practical activities